Implementasi Komunikasi Nonverbal Oleh Supeltas Perempatan Coyudan Guna Meningkatkan Kesadaran Dan Keselamatan Pengguna Jalan - Resha, Lidia Penta; Hindra H, Nurnawati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research focuses on the role of nonverbal communication in the context of traf ic at theCoyudan intersection, Surakarta City. This city has a high volume of vehicles, especiallyduring rush hours, which often causes traf ic jams. One solution implemented to overcome this problemis to involve Traf ic Control Volunteers (Supeltas) who use nonverbal movements to regulatevehicle flow and increase the safety of road users. The aim of this research is to find out hownonverbal communication is used by Surakarta City Traf ic Control Volunteers (Supeltas) toincrease awareness and safety of road users. The method used in this research is qualitative witha descriptive approach. Data collection was carried out through in-depth interviews, fieldobservations and documentation. The data sources for this research are interviewdata frominformants and literature. Research informants included Supeltas members and road users inthe Coyudan intersection area. The theory used in this research is the SMCR model introducedby David K. Berlo. This type of research is descriptive qualitative. Determining informantsusing purposive sampling. The research results were obtained after the researcher carriedoutthe data analysis stages, namely data collection, data reduction, data display, and verification. The research results show that the nonverbal movements implemented by Supeltas, including12 traf ic movements taught by Satlantas, are ef ective in regulating traf ic flowand increasingroad user awareness. In general, Supeltas plays an important role in creating safer andmoreorderly traf ic conditions through the use of nonverbal communication. Keywords: Nonverbal communication, Supervision, Road safety, Traf ic